PSIXOLOGIYALÍQ OYÍNLAR HÁM OLAR JÁRDEMINDE SHAHS ÓZGESHELIKLERIN QÁLIPLESTIRIW USÍLLARÍ - Klıcheva, Z.P. (SCIENCE and SOCIETY, 2024)
In this article given the examples of making an atmosphere of relationship and mutual trust between children and adults. For this purpose here geven sreicial organized psychological including a lot of psychological ganes and exereises.